KARYA MUSIK BAKISA DI LAPIAK NAN SALAI - Alfalah Alfalah (Institut Seni Indonesia Surakarta, 2011)
The work, entitled â€œBakisa in Lapiak Nan Salaiâ€ is presented in order to complete the study in Post- Graduate Program on Art Study and Composition at ISI Padangpanjang. This work was performed on January 1, 2011 in the Auditorium building Bustanoel Arifin Adam ISI Padangpanjang. The idea of this work is the description of the cultural life of the community charge Singgalang Tanah Datar, West Sumatra Province are always equal and balanced between earthly life and the hereafter. The balance can be seen in economic activity and religious traditions that are still patterned. In general, people Singgalang work in the fields or in the fields and mangilang taboo. From these observations, the phenomenon raised performer as basic starting point of departure or the creation of composition â€œin Lapiak Nan Bakisa Salaiâ€. were poured through both sound sources in the form of non-traditional instruments and traditions. Source of creation of this work are artt works and some of the paper, namely: Work of Elizar Koto â€œ Dialog Without Themeâ€ in 2000 (the writer has role as one of the musicians), â€œEncari Alternative 1â€, 1994 and â€œWaterâ€, 1996 . The work of Pande Made Sukerta â€œIf Music In ....â€, in 2008, the work of M. Halim â€œKraying Samailâ€, in 2007, by I Wayan Sadra titled â€œDroneâ€, in 2008, and works Asril Mukhtar titled â€œGentaâ€, in 2010. In addition there are several posts as a source of study, namely: description of work tasks Akhitr M. Halim titled â€œFanatic Bagurau Darek Minang people,â€ Mukhtar Asril entitled â€œSaluang and sangâ€ , Suka Harjanaâ€™s writings titled â€œThe writing of Contemporary Music, past and now, and the writing of Y. Sumandio Hadiyo Hadi â€˜The Art in Religion Ritualâ€™. The preparation of this work done the last ten stage works approved by the supervisor to be submitted as a final exam. The work is divided into 3 (three) parts, each of which has a different atmosphere, namely: the first part, has the atmosphere of peace, the second part of the atmosphere has faltered, and the third had a persistent atmosphere. Key words : â€œBakisa di Lapiak Nan Salaiâ€, Singgalang.